Compound heterozygosity for a whole gene deletion and p.R124C mutation in causing nonclassic congenital adrenal hyperplasia - Hamza Nasir; Syed Ibaad Ali; Naeem Haque; Stefan K. Grebe; Salman Kirmani (Annals of Pediatric Endocrinology & Metabolism, 2018)
We present a family with 2 members who received long-term steroid treatment for presumed classic congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency, until molecular testing revealed nonclassic CAH, not necessarily requiring treatment. A 17-year-old male presented to our clinic on glucocorticoid and mineralocorticoid treatment for classic CAH. He was diagnosed at 4 years of age based on mild-moderate elevations of 17-hydroxyprogesterone (17-OHP) and adrenocorticotropic hormone (ACTH), but without evidence of precocious adrenarche/puberty. Due to his diagnosis, his clinically asymptomatic 3-year-old sister was tested and also found to have elevated ACTH and 17-OHP levels and was started on glucocorticoids for classic CAH. Family history revealed a healthy sibling who had no biochemical evidence of CAH and consanguineous healthy parents. We questioned the diagnosis of classic CAH and performed an ACTH1-24 stimulation test, which showed a level of 17-OHP in the borderline range between classic and nonclassic CAH. Molecular testing, using sequencing and multiplex ligation-dependent probe amplification analysis of CYP21A2, revealed that both affected siblings were compound heterozygotes for a whole-gene deletion and a, likely pathogenic (nonclassical), sequence variant, p.R124C. The asymptomatic father had the same genotype, while the mother showed one deleted copy and 2 active copies, making her an asymptomatic carrier. Our report demonstrates the importance of molecular testing in atypical cases of CAH, as well as the importance of both sequencing and deletion analysis. The results of molecular testing should be interpreted in clinical context, and treatment should be prescribed according to guidelines when available.